(untitled) (Academic Journal of Internal Affairs, 2021)
Crime prevention is an obligation of a state. However, there are special areas where the state is unable to perform this obligation effectively on its own, therefore the difficulty of detection results in increased latency for specific crimes. Low detection efficiency motivates the continuation of commit these crimes, even if the legislator envisages high sanctions for the commission of the given conduct. Crudely sanctions would only act as a deterrent if the perpetrator of the crime could reasonably fear unconditional prosecution because of the high detection potential of the act. In the absence of this, increasing sanctions is not an optimal means of reducing latency, and thus of crime prevention. Such an area of detection challenge is also crime within the organization, as due to the closed, hierarchical structure of the organization, it is suitable to reveal illegal behaviors committed within its framework to the outside world, and thus to law enforcement authorities. It is therefore in the fundamental interest of the state to encourage organizations to prevent abuses within their framework, even if they otherwise serve the interests of the organization. The integrity approach promotes the morally clean operation of the organization and the individuals that are part of it, thus it is also a suitable system of tools to prevent the typically latent economic and corruption crimes committed within the organization. The study deals with organizational integrity in a criminological, more narrowly, crime prevention approach. After formulating the meaning of integrity from a criminological point of view, it deals with the relationship between integrity and compliance, and then with the question of what motivating factors make the organization to a source of danger at all, to a criminogenic area, and how to eliminate these factors. The final chapter of the study addresses the crime prevention relevance of integrity management tools.